Flugten ud af tiden - Beaujour, Michel (Passage - Tidsskrift for litteratur og kritik, 2010)
Michel Beaujour: "Flugten ud af tiden - Det poetiske sprog og revolutionen" Abstract Michel Beaujour: “Flight Out of Time: Poetic Language and the Revolution” The article – originally published in Yale French Studies in 1967 – investigates the possible relations between poetry and revolution, not least a number of contradictions and confusions inherent in many conceptions of such relationships.